2019
DOI: 10.1109/access.2019.2936133
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Visualization in Cardiology—A Systematic Review and Future Directions

Abstract: The digital transformations and use of healthcare information system, electronic medical records, wearable technology, and smart devices are increasing with the passage of time. A variety of sources of big data in healthcare are available, such as biometric data, registration data, electronic health record, medical imaging, patient reported data, biomarker data, clinical data, and administrative data. Visualization of data is a key tool for producing images, diagrams, or animations to convey messages from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The study was presented as an evidence for the researchers and practitioners to devise novel solutions in the area of interest. Nazir et al [ 13 ] presented a comprehensive review of the 10 years from 2008 to 2018 associated with the visualization of big data in the area of cardiology. The study identified 53 prospective papers related to visualization of big data in cardiology.…”
Section: Related Workmentioning
confidence: 99%
“…The study was presented as an evidence for the researchers and practitioners to devise novel solutions in the area of interest. Nazir et al [ 13 ] presented a comprehensive review of the 10 years from 2008 to 2018 associated with the visualization of big data in the area of cardiology. The study identified 53 prospective papers related to visualization of big data in cardiology.…”
Section: Related Workmentioning
confidence: 99%
“…A few of the well-known BDA techniques used in the areas of healthcare are described in Table 5. e categories provided in Table 5 are drawn from the literature [12,[66][67][68].…”
Section: Issues In Healthcare Bigmentioning
confidence: 99%
“…e categories that are generated in Table 5 are taken from the literature [12,[66][67][68]86]. Big data plays a significant role across all domains such as government organizations, trade associations, healthcare industries, education, and research and development.…”
Section: Big Data Analytical Techniques Inmentioning
confidence: 99%
“…In [5], big data visualization in cardiology domain is reviewed and the future research directions are discussed. A security model to preserve the medical big data privacy in healthcare cloud is presented on the basis of pairing based cryptography is presented in [6].…”
Section: Review Of Literaturementioning
confidence: 99%
“…This idea is imposed for choosing the cluster centre point, and the proposed clustering algorithm is presented as follows. The success probability is computed by equation (5), which is as follows.…”
Section: = || − ||mentioning
confidence: 99%